Parental Overprotection and Youth Anger Expression: The Mediating Role of Experiential Avoidance - Şahin, Ayşe; Soylu , Dilek (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The objective of this study was to examine the mediating role of experiential avoidance in the relationship between parental overprotection and anger expression among adolescents and young adults. Methods and Materials: This study used a descriptive–correlational design with a sample of 400 adolescents and young adults from Turkey, determined using the Krejcie and Morgan sampling table. Participants completed the State–Trait Anger Expression Inventory-2 (STAXI-2) to assess anger expression, the Acceptance and Action Questionnaire-II (AAQ-II) to measure experiential avoidance, and the Parental Bonding Instrument (PBI) to assess parental overprotection. Data were analyzed using SPSS-27 for descriptive and correlational analyses, and AMOS-21 for structural equation modeling (SEM). Findings: The results indicated that parental overprotection was positively correlated with both experiential avoidance (r = .42, p < .001) and anger expression (r = .39, p < .001). Experiential avoidance was also positively correlated with anger expression (r = .46, p < .001). SEM analyses revealed that parental overprotection significantly predicted experiential avoidance (b = 0.47, β = .42, p < .001), and experiential avoidance significantly predicted anger expression (b = 0.62, β = .44, p < .001). The direct path from parental overprotection to anger expression was significant (b = 0.28, β = .21, p < .001), and the indirect effect through experiential avoidance was also significant (b = 0.29, β = .18, p < .001). Conclusion: The findings suggest that experiential avoidance partially mediates the relationship between parental overprotection and anger expression, highlighting avoidance as a key transdiagnostic mechanism.